Pengaruh Modernisasi Administrasi Pajak Dan Sosialisasi Perpajakan Terhadap Tingkat Kepatuhan Wajib Pajak Di Kantor Pelayanan Pajak Pratama Pasar Minggu - Siti Solehah; Notika Rahmi (Jurnal Ilmu Administrasi Publik, 2023)
This study aimed to determine and analyze the effect of modernizing tax administration and socializing taxation simultaneously on the level of taxpayer compliance at KPP Pratama Pasar Minggu. The research method used was a quantitative, non-probability sampling technique, and the type of sample used was convenience sampling. The results of this study simultaneously showed that the results of Fhitung for the modernization of tax administration and tax socialization were 9.729 > Ftabe/ 3.938 (sig. 5% level) and a significance level of 0.000 was less than 0.05 (0.000<0.05), so it can be concluded that H3 was accepted, namely the variables of modernization of tax administration and tax socialization have a partially significant effect on taxpayer compliance. The percentage of the variable, 46.7%, was that modernization of tax administration and tax socialization have an impact on taxpayer compliance. It is suggested that KPP Pratama Pasar Minggu is expected to improve services and provide information effectively and efficiently.